LGBTIQ + identities in tourism and leisure research: a systematic qualitative literature review. Issue 7 (3rd July 2022) - Ong, Faith; Vorobjovas-Pinta, Oscar; Lewis, Clifford
Abstract: Tourism research on the LGBTIQ + communities has grown over the years, entering mainstream discussions as a segment of interest. This growing focus reflects greater societal acceptance and acknowledgement of the systemic inequalities that challenge their rights. The landscape of current scholarship, though important to academic literature, policy and practice, has not been explored. On this premise, and under the umbrella of social sustainability, a systematic qualitative review of scholarship on the LGBTIQ + community and tourism was conducted with Q1- and Q2-ranked travel and tourism journals (Scimago Journal & Country Rank) as a basis. Articles were analysed to identify the sampling parameters and their topic foci. The findings suggest the literature focuses on sexually diverse groups (gays and lesbians) who are open about their identity, with limited consideration given to bisexual or gender diverse travellers (intersex and transgender). The topics and language used have also evolved in recent years, transforming from earlier fixations on the sexual, to the exploration of other experiences related to the LGBTIQ + communities. This research reflects on this evolution, the implications for the broader queer communities, and proposes a research agenda for more robust inquiry concerning LGBTIQ + travel and leisure.